Utilization of oxidation-reduction reaction of Folin-Ciocalteu’s phenol reagent in colorimetric determination of amlodipine in pharmaceutical dosage form - Alshabrawy, Ali; Mostafa, Ahmed; Abotaleb, Nageh (European Journal of Chemistry, 2016)
A simple visible spectrophotometric method has been developed for determination of amlodipine in commercial tablets. Amlodipine (AMO) is 1,4-dihydropyridine derivative, this group when reacted with Folin-Ciocaluts phenol reagent in presence of 10% sodium carbonate, intense blue color was formed that exhibits maximum absorbance at wave length 745 nm. The intensity of color was found to be affected by many parameters. Optimization of the method parameters was done. The method was validated over a concentration range of 10 to 110 µg/mL. The values of each validation items were within the acceptable range for precision and accuracy. The lower limit for quantitation and lower of detection were founded to be 3.21 and 9.72 µg/mL, respectively. The proposed method was successfully applied to the quantitative determination of amlodipine in tablets without interference from tablet additives. The simplicity and accuracy of this method will allow many laboratories to determine the concentration of amlodipine in dosage form in easy way.